THE OPPOSITIONAL DUALITIES IN THE POETRY OF IBN MUJBIR AL-ANDALUSI (World Bulletin of Social Sciences, 2022)
Anti-dualism is a philosophical cosmic dualism that is dynamically linked to existence, and it represents a natural phenomenon in human life that shows the relationships that exist between existence, and the many difficulties that permeate human beings and his daily life. The aim of the research is to show the contradictions in the poetry of Ibn mujbir Al-Andalusi and try to identify their formations in his poetry. this study sought to reveal the phenomenon of the oppositional dualities that manifested themselves in the poetry of Ibn mujbir Al-Andalusi, taking different colors, between the individual and the composition or image that the poet intended to find a tangled world of relationships embraced by the poetic language. Since most of his hair was characterized by a lot of injuries in his hair, so it can be studied and find out the extent of their influence in his hair and find out the reasons that prompted him to use them in his hair, so his hair should be studied in this style.